Impact of the length of vitamin D deficiency on cardiac remodeling. - Assalin, Heloisa Balan; Rafacho, Bruna Paola; dos Santos, Priscila Portugal; Ardisson, Lidiane Paula; Roscani, Meliza Goi; Chiuso-Minicucci, Fernanda; Barbisan, Luis Fernando; Fernandes, Ana Angelica Henrique; Azevedo, Paula Schmidt; Minicucci, Marcos Ferreira; Zornoff, Leonardo Antonio; de Paiva, Sergio Alberto Rupp (Wolters Kluwer, 2013)
This study was aimed to evaluate the influence of vitamin D (VD) deficiency on cardiac metabolism, morphology, and function. Thus, we investigated the relationship of these changes with the length of the nutrient restriction. Male weanling Wistar rats were allocated into 4 groups: C2 (n=24), animals were fed an AIN-93G diet with 1000 IU VD/kg of chow and were kept under fluorescent light for 2 months; D2 (n=22), animals were fed a VD-deficient AIN-93G diet and were kept under incandescent light for 2 months; C4 (n=21) animals were kept in the same conditions of C2 for 4 months; and D4 (n=23) animals were kept in the same conditions of D2 for 4 months. Biochemical analyses showed lower β-hydroxyacyl coenzyme-A dehydrogenase activity and higher lactate dehydrogenase activity in VD-deficient animals. Furthermore, VD deficiency was related to increased cytokines release, oxidative stress, apoptosis, and fibrosis. Echocardiographic data showed left ventricular hypertrophy and lower fractional shortening and ejection fraction in VD-deficient animals. Difference became evident in the lactate dehydrogenase activity, left ventricular weight, right ventricle weight, and left ventricular mass after 4 months of VD deficiency. Our data indicate that VD deficiency is associated with energetic metabolic changes, cardiac inflammation, oxidative stress, fibrosis and apoptosis, cardiac hypertrophy, left chambers alterations, and systolic dysfunction. Furthermore, length of the restriction influenced these cardiac changes.
Keywords: caspase 3; connexin 43; connexin 43 protein, rat; lactate dehydrogenase; animal; cardiac remodeling; disease model; echography; heart left ventricle hypertrophy; heart ventricle; heart ventricle remodeling; male; metabolism; organ size; oxidative stress; pathology; pathophysiology; physiology; rat; time; vitamin D deficiency; Animals; Caspase 3; Connexin 43; Disease Models, Animal; Heart Ventricles; Hypertrophy, Left Ventricular; L-Lactate Dehydrogenase; Male; Organ Size; Oxidative Stress; Rats; Time Factors; Ventricular Remodeling; Vitamin D Deficiency